The Impact of Government Effectiveness and Political Stability on Energy Consumption in the Selected MENA Economies - Al-Tal, Raad; Al-Tarawneh, Alaaeddin (International Journal of Energy Economics and Policy, 2021)
This paper examines the impact of the quality governance on the energy sector in the MENA region, particularly, political stability and government effectiveness. Several macroeconomic variables are taken into account in a panel analysis, and the study employs the POLS and Fixed effect approaches to find out if the government’s effectiveness and political stability among all governance indicators have a vital role in promoting energy efficiency in MENA. Panel data for the period 2003-2018 are used. The empirical results show he political stability and the effectiveness of government are positively affected the energy consumption for the MENA countries. Moreover, the findings of the study show a negative relationship between energy consumption and economic growth. This situation referred to the unimproved relationship in the MENA region, as literature confirms no relationship exists for some countries in the region. Keywords: Energy Consumption; Quality Governance; Political Stability; Government Effectiveness; POLS; Fixed Effect; MENA. JEL Classifications: H11; Q38; Q43 DOI: https://doi.org/10.32479/ijeep.10786